1999
DOI: 10.1890/0012-9658(1999)080[2151:pinaap]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Patterns in Nutrient Availability and Plant Diversity of Temperate North American Wetlands

Abstract: Few wetland studies from temperate North America have related either species richness or plant community composition to any direct measure of nutrient availability, or examined changes in species composition following experimental nutrient additions. Studies of wetlands in western Europe and of other terrestrial ecosystems in North America frequently show that nutrient enrichment leads to changes in species composition, declines in overall plant species diversity, and loss of rare and uncommon species. We ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
185
3
8

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 440 publications
(212 citation statements)
references
References 92 publications
(150 reference statements)
16
185
3
8
Order By: Relevance
“…also reported low foliar P concentrations for wetland vegetation in China compared to global averages 29 . Low P levels might be due to P in the soil being highly insoluble compared to N. Furthermore, a dense root system is usually needed for plants to extract significant amounts of P from soil 13 . However, in Dongting Lake, these 3 macrophyte species tend to have shallow root systems to acclimate to flooding stresses, which might be unfavourable for P absorption.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…also reported low foliar P concentrations for wetland vegetation in China compared to global averages 29 . Low P levels might be due to P in the soil being highly insoluble compared to N. Furthermore, a dense root system is usually needed for plants to extract significant amounts of P from soil 13 . However, in Dongting Lake, these 3 macrophyte species tend to have shallow root systems to acclimate to flooding stresses, which might be unfavourable for P absorption.…”
Section: Discussionmentioning
confidence: 99%
“…In some North American wetlands, the structure of plant communities changes significantly with nutrient gradients, while species richness declines with increasing nutrient availability 13 . The Resource Ratio Hypothesis suggests that when the limiting resource in a given vegetation community changes, the dominant species changes due to altered growth performance and competition.…”
Section: Introductionmentioning
confidence: 99%
“…On 30 May 2006, seedlings were transplanted into individual plastic pots (30 cm diameter 9 25 cm deep), and placed in plastic wading pools (1.4 m diameter 9 30 cm deep). The pots contained Sunshine LC1 potting soil (Sun Gro Horticulture Canada, Seba Beach, AB, Canada), which has an initial nutrient charge that would correspond to high nutrient levels found in natural wetland soils, i.e., approximating three times the average N content (Bridgham et al 1996;Bedford et al 1999). Because that initial charge is highly water-soluble and provides the equivalent of approximately one application of a liquid fertilizer (Sun Gro Horticulture, personal communication), nutrients were supplemented as described below.…”
Section: Study Populations and Common Garden Experimentsmentioning
confidence: 99%
“…The Osmocote applied in the high-nutrient treatment followed the manufacturer's recommendation for the amount and rate that is generally used to achieve high levels of fertilization (i.e., one application for the 3-to 4-month growing period). Consequently, the low-and high-nutrient treatments were designed to be reasonable approximations of nutrient levels that would be encountered under natural field conditions (cf., Bridgham et al 1996;Thormann and Bayley 1997;Bedford et al 1999). The date of first flowering by each plant was recorded throughout the experimental period.…”
Section: Study Populations and Common Garden Experimentsmentioning
confidence: 99%
“…There is evidence that F. alnus alters nutrient properties in white-pine (Pinus strobus L.) dominated uplands (Fagan and Peart 2004) and has been associated with higher nitrogen levels in hardwood dominated uplands (Huebner et al 2009), but we found no published data on its effect on nutrients in wetlands. Increasing eutrophication of wetlands in North America may lead to decreased species richness within wetlands (Bedford et al 1999). Increased nutrient availability as a result of F. alnus invasion is more likely in this case than larger scale eutrophication leading to decreased species richness, since both uninvaded areas are within 25 m of invaded areas.…”
Section: Nutrient Availabilitymentioning
confidence: 99%